Ag/AgBr-loaded mesoporous silica for rapid sterilization and promotion of wound healing. (29th May 2018) - Jin, Chen; Liu, Xiangmei; Tan, Lei; Cui, Zhenduo; Yang, Xianjin; Zheng, Yufeng; Yeung, Kelvin Wai Kwok; Chu, Paul K.; Wu, Shuilin
Abstract : Bacterial infection is a major concern during the wound healing process. Abstract : Bacterial infection is a major concern during the wound healing process. Herein, Ag/AgBr-loaded mesoporous silica nanoparticles (Ag/AgBr/MSNs) are designed to harvest visible light for rapid sterilization and acceleration of wound healing. The Ag/AgBr nanostructure has remarkable photocatalysis ability due to the critical factor that it can generate electron–hole pairs easily after light absorption. This remarkable photocatalytic effect enhances the antibacterial activity by producing reactive oxygen species (ROS). The bacterial killing efficiency of Ag/AgBr/MSNs is 95.62% and 99.99% against Staphylococcus aureus and Escherichia coli, respectively, within 15 min under simulated solar light irradiation due to the generation of ROS. Furthermore, the composites can arrest the bacterial growth and damage the bacterial membrane through electrostatic interaction. The gradual release of Ag + not only prevents bacterial infection with good long-term effectiveness but also stimulates the immune function to produce a large number of white blood cells and neutrophils, which favors the promotion of the wound healing process. This platform provides an effective strategy to prevent bacterial infection during wound healing.